Enhancement of FSR and finesse using add/drop filter and panda ring resonator systems - Amiri, Shervin (2012)
We present effect of the input central wavelength on microring resonator (MRR) performance using proposed systems. The first proposed system consists of series of microring resonator incorporated with an add/drop filter system, while the second system uses a PANDA ring resonator connected to an add/drop filter system. These two systems can be used to enhance the free spectrum range (FSR) and finesse (F) of the optical soliton pulses. The FSR and Finesse can be improved by raising the central wavelengths of the input pulse from 0.6 μm to 1.5 μm. This is obtained via the add/drop filter, which is used to increase the channel capacity of the communication networks as well. Simulation results for the first proposed system show that FSR and FWHM of 1530 pm and 50 pm can be obtained when the central wavelength of the input pulse is 1.5 μm. FSR and FWHM of 370 pm and 5 pm are simulated, when the PANDA ring resonator system is used. Therefore Finesse of the systems can be improved to 30.6 and 74 for the first and second proposed system, respectively.